ANALISIS RENTABILITAS PADA PT. SEPATU BATA.Tbk INDONESIA - -, Tarmidi - (EKONOMIA, 2015)
Economic development in general requires a better economy or more advanced. Better economic conditions that are required in all areas, including in the management of the company. One factor that determines the development of the company tergantunng on good financial management system and efficient.This study authors took data on the Jakarta stock exchange, on the PT shoes Bata Tbk The purpose of this study was to determine Ability labaan PT shoes Bata Tbk in years 2010-2012 are increased.The method used in this research is descriptive method. Source of data in this study is derived from the financial statements of PT Sepatu Bata Tbk, Indonesia 2010-2012. For data analysis techniques, used analysis of the profitability ratio that focuses on economic profitability (RE) and the profitability of its own capital (RMS).Based on the results of the description and analysis has been done, then the hypothesis is accepted for Economic Profitability between RE and RMS in 2010 to the year 2011 has decreased and in 2011 to the year 2012 has increased